Development of cytochrome-c oxidase activity in rat heart: downregulation in newborn rats - Drahota, Z; Milerova, M; Stieglerova, A; Skarka, L; Houstek, J; Ostadal, B (Cell biochemistry and biophysics, 2005)
Cytochrome-c oxidase (COX) activity of the rat heart was two- to sevenfold activated when the membrane integrity was disrupted by hypotonic swelling, freezing-thawing, or a detergent, indicating that a large portion of COX capacity in intact mitochondria is not active. The effect of detergent was tested in heart mitochondria isolated from 1-, 5-, 15-, 29-, and 60-d-old rats; activation by detergent was up to 20-fold in 1-d-old animals, whereas in mitochondria from 60-d-old rats it was only 7-fold. Our data indicate that the rat heart exhibits significant developmental changes dependent on downregulation of COX activity in the neonatal period.
Keywords: regulace genové exprese enzymů; Down-Regulation; Mitochondria, Heart; novorozená zvířata; stárnutí; krysa rodu Rattus; srdeční mitochondrie; zvířata; Enzyme Activation; Cells, Cultured; Aging; down regulace; potkani Wistar; Gene Expression Regulation, Developmental; Animals, Newborn; Rats, Wistar; respirační komplex IV; Male; detergenty; kultivované buňky; Heart; Rats; Gene Expression Regulation, Enzymologic; myokard; Electron Transport Complex IV; vývojová regulace genové exprese; Animals; aktivace enzymů; Myocardium; mužské pohlaví; Detergents; srdce